(untitled) - Smalley, Regina L. (Australia, 2012)
Combines comprehensive development and practice in the rhetorical modes while integrating instruction in reading, grammar, critical thinking, and vocabulary development. This title focuses students on narrating, describing, analyzing, comparing and contrasting, classifying, and evaluating at the paragraph level.
Keywords: Tiếng Anh,English language; Tu từ học,Rhetoric